A study of the different treatment modalities used in the management of amoebic liver abscesses - Garale, Mahadeo N.; Takalkar, Yogesh P.; Ingale, Parag R. (International Surgery Journal, 2016)
Background: Amoebic liver abscess (ALA) is the most common extra intestinal manifestation of amoebiasis and is very common in the Indian subcontinent. ALA occurs in 3%-9% of patients with Entamoeba histolytica infection. Treatment modalities offered along with anti-amoebic medications are Guided percutaneous aspiration, Guided percutaneous drainage and Surgery. To study the indications and outcomes viz. symptomatic relief and resolution of clinical signs, resolution of the abscess, morbidity and mortality of the treatment modalities used for management of amoebic liver abscesses. Methods: This observational study included 100 patients diagnosed to harbour amoebic liver abscess. All the patients received metronidazole orally or intravenously in appropriate dose. Percutaneous aspiration (PCA) was used for impending rupture on ultasonography (rim <10 mm), left lobe abscess, failure of medical management. Percutaneous catheter drainage (PCD) was performed for abscesses more than 150 cc, abscess with localised rupture and failure of medical management. Surgery was treatment offered in generalised peritonitis. Analysis pertaining to reduction of volume, duration of stay, morbidity and mortality was done for each modality. Results: Of the 100 patients, 33 were treated conservatively with medications alone with failure in 5 patients, 18 treated by percutaneous aspiration, 48 by percutaneous insertion of drain and 6 by surgery for ruptured abscess with generalised peritonitis. The mean duration of hospital stay in PCA group was 5.8 days while it was 9.12 days in PCD group. Bleeding (n=4) and bile leak (n=2) while bile leak (n=4) and death (n=2) were the complications reported in patients undergoing PCD and surgery, respectively. Conclusions: In Amoebic liver abscess PCA or PCD offers better and accelerated reduction in volume of abscess cavity with treatable morbidity and without fear of mortality and surgery can be avoided in these patients.